Dampak Politik Pencitraan (Imagologi) Terhadap Kontestasi Politik di Indonesia - Agus, Rizka Bintang; Abd. Hadi (Universitas Sunan Drajat Lamongan, Indonesia, 2023)
This research is intended about how the implementation of the recruitment process for the management of political parties in finding administrators in its implementation refers to the political party law number 2 of 2011, in general political parties are a key to the success of a country's political system, and the most important key is the recruitment of cadres and political party administrators, which is an important indicator to see the changes and development of a political party in building a political system in the government of a country. But in practice the process of recruiting cadres and party officials still violates the rules as regulated in the Act. Number 2 of 2011 concerning political parties. An example of the phenomenon that is currently booming is that artists are busy being registered as legislative candidates by political parties, which is evidence of the failure of political parties to carry out regeneration. So that political parties take shortcuts by exploiting the popularity of artists to gain votes in legislative elections and this certainly has a negative impact on democracy in Indonesia. This research is focused on how the procedures of political parties in recruiting their cadres in finding and occupying political party management positions in a democratic manner or more on a nepotistic approach. looking for management. Research Methods The research used is descriptive analytical. The results of the study, examining from a legal perspective based on the rules of law No. 2 of 2011 concerning political parties and the Articles of Association and Bylaws of political parties, in this study concludes that as in recruiting for positions of administrators, many political parties do it in a way that does not democratic positions, such as positions that have significant influence in political parties, such as the positions of DPD Chair, DPC Chair, Treasurer, Secretary General of the party to the general chairman of political parties. So that it has implications for the electability of political parties and the image of political parties is bad and undemocratic. This research is focused on how the procedures of political parties in recruiting their cadres in finding and occupying political party management positions in a democratic manner or more on a nepotistic approach. looking for management. Research Methods The research used is descriptive analytical. The results of the study, examining from a legal perspective based on the rules of law No. 2 of 2011 concerning political parties and the Articles of Association and Bylaws of political parties, in this study concludes that as in recruiting for positions of administrators, many political parties do it in a way that does not democratic positions, such as positions that have significant influence in political parties, such as the positions of DPD Chair, DPC Chair, Treasurer, Secretary General of the party to the general chairman of political parties. So that it has implications for the electability of political parties and the image of political parties is bad and undemocratic.